Commodification of Poverty in Social Media - Azmi, Bela Fataya; Astari, Devi Wening (SEMIOTIKA: Jurnal Komunikasi, 2024)
The commodification of poverty is no longer only capable of being carried out by the mass media. In the digital era, people can use poverty as content or commodify poverty through social media. Commodification using poverty as a social media selling point often occurs and continues to be repeated. This research aims to read the commodification of poverty on social media in Indonesia by analyzing the content of the Instagram accounts @hestyprw and @bella_saskya8 using a qualitative content analysis approach. Roland Barthes' semiotics, which includes denotation, connotation, and myth, is used as a research method in dissecting research objects (verbal and visual signs). The research found that both Instagram accounts used symbols of poverty, such as low-income family backgrounds and jobs, simple to damaged housing, and narratives of life's difficulties as the central concept of their content. On the other hand, the research also found a conflict between the content created by the two accounts, where the forms of poverty narrated were in contrast to the content creator's visual image (wearing nice clothes and even gold jewelry). Thus, the commodification of poverty carried out on social media is different from the commodification of poverty in mass media, where commodification on social media is more of a fake show and is directed at seeking attention, even debate so that the audience becomes increasingly curious about following the content.